Woodball Game Technique Skills Test Model for South Sumatra Athletes - Kumbara, Hengki; Okilanda, Ardo; Putra, Dede Dwiansyah (Universitas PGRI Palembang, 2024)
The aim of the research is to produce a test model for woodball game technique skills for South Sumatran woodball athletes. This test model is adapted to the match patterns and playing techniques of South Sumatran woodball athletes. This type of research is research and development using the Sugiyono model. The small scale trial consisted of 9 IGM club athletes, the large scale total of all South Sumatra woodball athletes was 12 people. Data collection uses interview sheets, value scales, test effectiveness observation sheets and test result data sheets. The data analysis technique uses quantitative descriptive analysis. The results of the research are a form of woodball game technical skills test as outlined in the woodball game technical skills test manual consisting of long area, parking area and shoot on the gate tests. Testing the validity of the test instrument produces a correlation coefficient of 0.915 with valid criteria. Testing the reliability of the test produces a correlation coefficient of 0.928 with reliable information. The evaluation carried out by material experts can be concluded that the woodball game technique skill test model is suitable for use for South Sumatra woodball athletes.